The Nguyen Dynasty with the Aesthetic Value of Bronze Relics in Hue - Chung, Phan Le; Le, Nguyen Thi Hien; Huy, Dinh Tran Ngoc (Journal of Public Representative and Society Provision, 2022)
The purpose of this paper is to review the Nguyen dynasty by using the element of visual sense with bronze relics in Hue. The method using observations, experience, synthesis analysis, historical and dialectical methods and draws some educational lessons for students. From the above findings it is clear that Copper material is also one of the used most in objects that are related to religious material such as bronze bells, bronze bells, etc. Finally is the esthetic value of the decorative art on bronze in Hue is also the blending of the basic elements and the integration of the cultural factors.